Ectomycorrhizal fungal response to warming is linked to poor host performance at the boreal‐temperate ecotone. (18th December 2016) - Fernandez, Christopher W.; Nguyen, Nhu H.; Stefanski, Artur; Han, Ying; Hobbie, Sarah E.; Montgomery, Rebecca A.; Reich, Peter B.; Kennedy, Peter G.
Abstract: Rising temperatures associated with climate change have been shown to negatively affect the photosynthetic rates of boreal forest tree saplings at their southern range limits. To quantify the responses of ectomycorrhizal (EM) fungal communities associated with poorly performing hosts, we sampled the roots of Betula papyrifera and Abies balsamea saplings growing in the B4Warmed (Boreal Forest Warming at an Ecotone in Danger) experiment. EM fungi on the root systems of both hosts were compared from ambient and +3.4 °C air and soil warmed plots at two sites in northern Minnesota. EM fungal communities were assessed with high‐throughput sequencing along with measures of plant photosynthesis, soil temperature, moisture, and nitrogen. Warming selectively altered EM fungal community composition at both the phylum and genus levels, but had no significant effect on EM fungal operational taxonomic unit (OTU) diversity. Notably, warming strongly favored EM Ascomycetes and EM fungi with short‐contact hyphal exploration types. Declining host photosynthetic rates were also significantly inversely correlated with EM Ascomycete and EM short‐contact exploration type abundance, which may reflect a shift to less carbon demanding fungi due to lower photosynthetic capacity. Given the variation in EM host responses to warming, both within and between ecosystems, better understanding the link between host performance and EM fungal community structure will to clarify how climate change effects cascade belowground.